Evidence for multiple founding lineages and genetic admixture in the evolution of species within an oceanic island weevil (Coleoptera, Curculionidae) super-radiation - Faria, Christiana (2018)
AIM: To infer colonization and speciation history for a closely related complex of nine species within the enigmatic Canary Island Laparocerus weevil radiation of 128 species. Using molecular dating and the spatial and temporal context that islands provide, we evaluate the possible explanations of incomplete lineage sorting and gene flow for the origin of shared genetic variation among species from different islands. LOCATION: Canary Islands (Gran Canaria, Tenerife, La Palma and El Hierro). METHODS: We collected a total of 173 specimens from 37 sites distributed across the four islands. Phylogenetic analyses of mitochondrial (COII) and nuclear (ITS2) sequence data and molecular dating techniques were used to infer the origin of the group in the archipelago and their history of colonization and differentiation. RESULTS: Gran Canaria appeared to be the geographical origin of the complex. An unexpected result was that mtDNA revealed each of the single species on La Palma and El Hierro to be the product of more than one colonization event from more than one source island. In both cases nuclear ITS2 data revealed these multiple colonizations to have been followed by admixture. MAIN CONCLUSIONS: The two gene trees present very different topologies, with a rather simple colonization history required to explain the pattern of nuclear gene relationships, while the mtDNA gene tree implicates a much more complex history of colonization. Explanations of incomplete lineage sorting are ruled out and a history of colonization and speciation for the L. tessellatus complex involving genetic admixture is inferred.